Scaling solutions in the derivative expansion - Defenu, Nicolò; Codello, Alessandro (Arxiv, 2017)
Scalar field theories with $\mathbb{Z}_{2}$-symmetry are the traditional playground of critical phenomena. In this work these models are studied using functional renormalization group (FRG) equations at order $\partial^2$ of the derivative expansion and, differently from previous approaches, the spike plot technique is employed to find the relative scaling solutions in two and three dimensions. The anomalous dimension of the first few universality classes in
Gesehen am 08.12.2020